IS THE DISTRIBUTION OF GERIATRIC INFECTIONS DIFFERENT IN EASTERN TURKEY? RETROSPECTIVE EVALUATION OF GERIATRIC INFECTIONS - Sagmak Tartar, Ayse; Balin, Safak Ozer; Akbulut, Ayhan (Gunes Kitabevi Ltd Sti, 2018)
Introduction: Infections are one of the most important reasons for hospitalization, morbidity and mortality among geriatric patients. Materials and Method: Between June 2016 and December 2017, patients aged 65 and older who were hospitalized for treatment were retrospectively evaluated at the infectious diseases and clinical microbiology department of Firat University Hospital. Results: In total, 900 patients were admitted to our clinic. Of these, 350 (38.8%) of these patients were over 65 years old; 218 (62.3%) were male and 132 (37.7%) were female. The most common reasons for hospitalization were pyelonephritis in 109 patients (31.5%), pneumonia in 78 (22.2%), cystitis in 72 (20.6%) and skin and soft-tissue infection in 32 (9.3%). Extrapulmonary tuberculosis, brucellosis, Crimean Congo haemorrhagic fever, fascioliasis and cutaneous leishmaniasis were the prominent causes of hospitalization. Hypertension and diabetes mellitus were the most common comorbidities. Combination antibiotics were administered to 95 (27.4%) patients, whereas 251 patients received a single antibiotic. Of 245 (70%) patients who required consultation with various departments, 77 (20%) consulted with neurology, 68 (19.4%) with urology and 44 (12.5%) with chest diseases departments. Radiological imaging, most commonly abdominal ultrasound, was performed in 228 (65.1%) patients. Blood infection was detected in 31 patients. Conclusion: In areas such as our region, where many infectious diseases are endemic, diseases, such as tuberculosis, brucellosis, parasitic diseases, or Crimean Congo haemorrhagic fever, can occur in elderly individuals. Therefore, a multidisciplinary approach is essential to evaluate geriatric infections and a radiologist should be included in this multidisciplinary team.
Türkiye’nin doğu bölgesinde geriatrik infeksiyonlarin dağilimi farkli mi? Geriatrik infeksiyonlarin retrospektif değerlendirilmesi
Keywords: Infection; Geriatrcis; Tuberculosis; Referral and consultation